2012
DOI: 10.1074/jbc.m111.277061
|View full text |Cite
|
Sign up to set email alerts
|

Exosome-associated Tau Is Secreted in Tauopathy Models and Is Selectively Phosphorylated in Cerebrospinal Fluid in Early Alzheimer Disease

Abstract: Background: Tau is secreted unconventionally, possibly explaining increased CSF phosphotau levels in early AD. Results: M1C cells secrete selectively phosphorylated, exosomal tau. These characteristics in early AD CSF tau suggest that CSF tau is secreted, not shed from dead neurons. Conclusion: Tau secretion occurs early and may explain lesion spreading in AD. Significance: Secretion biomarkers may become revolutionary prospective AD diagnostics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
783
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 835 publications
(826 citation statements)
references
References 48 publications
16
783
1
4
Order By: Relevance
“…Exocytosis by conventional exosomes, as a result of the fusion of multivesicular bodies with the plasma membrane, has been reported for monomeric A␤ (17), ␣-synuclein (18 -20), PrpSc (2,21), and Tau (22) in neuroblastoma cell lines. Other unconventional exocytosis mechanisms have been described for PrP (23) and ␣-synuclein (19).…”
mentioning
confidence: 99%
“…Exocytosis by conventional exosomes, as a result of the fusion of multivesicular bodies with the plasma membrane, has been reported for monomeric A␤ (17), ␣-synuclein (18 -20), PrpSc (2,21), and Tau (22) in neuroblastoma cell lines. Other unconventional exocytosis mechanisms have been described for PrP (23) and ␣-synuclein (19).…”
mentioning
confidence: 99%
“…2 Several explanations have been proposed for tau release. These include unconventional secretion directly into the media [53,54], vesicle-associated release [56] and exosomeassociated release [57,58]. While certain studies show a subset of secreted tau is found in the exosomal fraction of conditioned media [58], others show little to no tau in this fraction [53,54].…”
Section: Escape Of Aggregates From Neuronsmentioning
confidence: 99%
“…In AD, tau becomes hyperphosphorylated and misfolded at both terminals, and the accumulation of hyperphosphorylated oligomers at synapses is associated with increased ubiquitinated substrates and increased proteasome components, consistent with dysfunction of the ubiquitin-proteasome system. In addition, Saman et al [24] demonstrated that exosome-associated tau is present in human CSF, and is phosphorylated at Thr-181, suggesting that exosome-mediated secretion of phosphorylated tau may play a role in the abnormal processing of tau and in the genesis of elevated tau levels in CSF in early AD.…”
Section: Research Aspectsmentioning
confidence: 99%